Evidence of uses of marine litter by Mediterranean Cephalopoda - Capillo, Gioele; Albano, Marco; D’Iglio, Claudio; Famulari, Sergio; Di Fresco, Dario; Spanò, Nunziacarla; Savoca, Serena (Frontiers in Marine Science, 2024)
Understanding the interaction between marine biota and marine litter is essential to comprehend how organisms face the continuous alteration of their habitats due to anthropogenic pressure. The evidence here reported, based on both direct in situ observations and citizen science obtained information, refer to the interactions between two Mediterranean Cephalopoda species and marine litter in natural environments, and, more specifically, between: i) Octopus vulgaris and a plastic bin used for laying eggs inside, ii) Sepia officinalis and an artificial Egi lure, used for oviposition, iii) another specimen of O. vulgaris and an artificial lure, used for den enhancing. This highlights marine litter presence, probably joint with the scarcity of natural substrates, could lead to a behavioural adaptation of the species in responding to the reproductive stimulus, especially in the case of semelparous species. Based on these individual observations it is undoubtedly of crucial importance improving the knowledge base on the relationship between marine biota - marine litter and effects on marine animals and offspring.